Respuesta :
2Ag⁺(aq) + Mg(s)→ 2Ag(s) + Mg²⁺ (aq)
Further explanation
Given
Standard cell notation:
Mg(s) | Mg2+ (aq) || Ag+(aq)| Ag(s)
Required
a balanced redox reaction
Solution
At the cathode the reduction reaction occurs, the anode oxidation reaction occurs
In reaction:
Ag⁺ + Mg → Ag + Mg²⁺
half-reactions
- at the cathode (reduction reaction)
Ag⁺ (aq) + e⁻ ---> Ag (s) x2
2Ag⁺ (aq) + 2e⁻ ---> 2Ag (s)
- at the anode (oxidation reaction)
Mg (s) → Mg²⁺ (aq) + 2e−
a balanced cell reaction
2Ag⁺(aq) + Mg(s)→ 2Ag(s) + Mg²⁺ (aq)